The seven dimensions of Skunk Works: a new approach and what makes it unique. Issue 1 (8th July 2019) - Larsson, Anthony
Abstract : Purpose: This paper aims to study the definition and formation of Skunk Works and how it may present itself as a viable theoretical alternative to other mainstream concepts of collective/corporate entrepreneurships, while dissecting some of the prevalent misconceptions of the extant literature regarding the application of Skunk Works. Design/methodology/approach: This is a literature-based conceptual study that compares and differentiates various forms of group entrepreneurships as discussed in the academic debate. Findings: This study shows how Skunk Works differs from other forms of collective/corporate entrepreneurship through its seven dimensions (isolation, customer needs, focus, planning, trusted project manager, cross-functional teams and leveraging overlaps) while challenging the dominant extant contenders of collective/corporate entrepreneurship. Practical implications: Skunk Works remains a sustainable form of entrepreneurship, and it is still viable to consider it as a practical construct for smaller as well as larger organisations as a means of solving complicated innovative tasks requiring a multidisciplinary team with expert competence in a relatively quicker period of time. Social implications: Organisations may take greater initiatives towards assembling entrepreneurial teams in the Skunk Work tradition. Originality/value: As a means of understanding collective/corporate entrepreneurship, this study dissects some of the original fundamental cornerstones of Skunk Works entrepreneurship in an effort to present it as a viable alternative construct to the dominant construct of entrepreneurial orientation as well as other extant constructs.